Respiratory Distress and Its Outcome among Neonates Admitted to Neonatal Intensive Care Unit of Mukalla Maternity and Child Hospital, Yemen - Saleh Awad Bahwal; Mazin Ahmed Jawass; Ali Salim Bahartha (Diyala Journal of Medicine, 2020)
Background: Respiratory distress is one of the most common causes of admission in neonatal intensive care unit .